Survey errors and survey costs - Groves, Robert M. (New York : Wiley, 1989)
This book synthesize the statistical and social science perspective to produce a more complete treatment of survey errors and cost of alternative survey designs.
Includes bibliographical references (p. 553-579) and index.
ijb, 14/01/2019
Loans
Keywords: Household surveys; Social surveys